Role of tranexamic acid in reducing blood loss in vaginal delivery - Kaur, Harsimran; Kaur, Amrit Pal; Grover, Suparna; Jyothi (International Journal of Research in Medical Sciences, 2024)
Background: Postpartum hemorrhage (PPH) remains a significant reason for maternal death, especially in developing nations like India, where it accounts for 23% of maternal deaths. This prospective study aimed to assess the effectiveness of tranexamic acid (TXA) in reduction of blood loss during vaginal deliveries. Methods: This study was conducted at Bebe Nanki mother and child care centre in Amritsar, Punjab. 200 pregnant women were randomly assigned to two groups: Group A received 1g TXA intravenously alongside 10 IU oxytocin intramuscularly, while group B received only oxytocin. The measurement of blood loss was done up to 2 hours post-delivery along with various vital and hemodynamic parameters. Results: The results showed reduction in blood loss in group A in comparison to Group B which was significant, with mean blood loss of 106.25 mL in group A vs 222.45 mL in group B (p=0.001). Hb and PCV declines were also significantly lower in group A. Fewer patients in group A required additional uterotonics (4%) or blood transfusions (2%) versus group B (26% and 4%, respectively). No significant adverse effects, such as thromboembolic events, were observed in either group. Mild post-delivery nausea and vomiting was seen in both groups, with slightly higher incidence in group A. Conclusions: TXA combined with oxytocin significantly reduces postpartum blood loss without major side effects, supporting its use as an adjunct therapy in PPH management. Further studies are recommended to validate these findings and promote wider adoption in clinical practice.